2019
DOI: 10.1021/acssuschemeng.9b04424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on CO2 Capture by Aprotic Heterocyclic Anion (AHA) Ionic Liquids

Abstract: The reaction between three aprotic heterocyclic anion (AHA) ionic liquids (ILs) (triethyl(octyl)phosphonium 2-cyanopyrrolide [P 2228 ]-[2CNPyr], triethylphosphonium benzimidazolide [P 2222 ][BnIm], and triethyl-(octyl)phosphonium indazolide [P 2228 ][Inda]) and CO 2 , in the presence of water, is investigated in this study. We propose a reaction mechanism where, in addition to the reaction of the anion with CO 2 to form carbamate, the anion reacts with water (i.e., hydronium ions in water from either the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…At present, to improve the performance of AILs-catalyzed carboxylative cyclization of PA with CO 2 , the most popular strategy is to tune the basicity of AILs to enhance the interaction between AILs and PA or CO 2 . Generally speaking, as the basicity of AILs increases, the interaction between AILs and CO 2 increases, resulting in an increase in CO 2 absorption and higher absorption enthalpy. Surprisingly, as the basicity of AILs increased, the conversion of PA increased accordingly as expected, and the yield of α-alkylidene cyclic carbonate products increased first and then decreased. Wang and co-workers investigated with DFT calculations how the basicity of AILs (quantified by the p K a of the azole-based anions in t BuOH) affects the conversion of PA and the yield of alkylidene carbonates (Figure ).…”
Section: Introductionmentioning
confidence: 81%
“…At present, to improve the performance of AILs-catalyzed carboxylative cyclization of PA with CO 2 , the most popular strategy is to tune the basicity of AILs to enhance the interaction between AILs and PA or CO 2 . Generally speaking, as the basicity of AILs increases, the interaction between AILs and CO 2 increases, resulting in an increase in CO 2 absorption and higher absorption enthalpy. Surprisingly, as the basicity of AILs increased, the conversion of PA increased accordingly as expected, and the yield of α-alkylidene cyclic carbonate products increased first and then decreased. Wang and co-workers investigated with DFT calculations how the basicity of AILs (quantified by the p K a of the azole-based anions in t BuOH) affects the conversion of PA and the yield of alkylidene carbonates (Figure ).…”
Section: Introductionmentioning
confidence: 81%
“…We also assume that water is removed prior to the CO 2 capture process by a flue gas dehydration treatment. However, the effect of water is interesting since recent studies have shown that water has a favorable effect on CO 2 absorption by AHA ILs. , Thus, developing a reliable thermodynamic model for this phenomenon is a topic of interest. A further discussion of the impact of water absorption on the process performance has been presented by Hong et al .…”
Section: Flowsheet Modelingmentioning
confidence: 99%
“…We have developed a class of ILs for CO 2 capture that contain aprotic heterocyclic anions (AHA). They react stoichiometrically and reversibly with CO 2 with almost no increase in viscosity. We have shown that they can be encapsulated to increase mass transfer area, while maintaining reversibility, and have investigated the reaction chemistry that takes place when water is present . In that case bicarbonate is formed along with the carbamate.…”
Section: Introductionmentioning
confidence: 99%